A method for detecting titanium content in silicon-aluminum alloy
By mixing and grinding anhydrous sodium carbonate and boric acid and quickly melting at high temperature, the problem of environmental pollution and rapid analysis inability to detect titanium content in silicon-aluminum alloys is solved, and efficient and accurate titanium content detection is achieved.
Patent Information
- Application Number
- CN202411805752.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing titanium content detection methods in silicon-aluminum alloys have problems such as environmental pollution and inconvenient sample analysis.
The mixture was mixed with anhydrous sodium carbonate and boric acid, and the sample was quickly melted at high temperature. The melt was leaching through nitric acid. Diantipirin methane was used as the color developer. The solution absorbance was measured by spectrophotometry and the content of titanium was calculated.
This method is easy to operate, uses less medicines and equipment, has high detection efficiency and high accuracy, and is suitable for rapid batch testing.
Smart Images

Figure CN119269489B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium content detection, and in particular to a method for detecting the titanium content in a silicon-aluminum alloy. Background Art
[0002] Silicon aluminum alloy is a commonly used light alloy. It is widely used in the automotive, aerospace, electronics and construction industries due to its good casting performance, wear resistance and corrosion resistance. Silicon added to aluminum alloy is the main component to improve fluidity. Silicon and aluminum can form a solid solution, improve the high-temperature moldability of the alloy, and reduce elongation. When the silicon content in the alloy exceeds the eutectic component, that is, hard spots of free silicon appear, it will make cutting difficult, so the silicon content should be strictly controlled. In summary, the accurate detection of the chemical composition of silicon is particularly important for the performance of aluminum alloys.
[0003] During the smelting process of silicon-aluminum alloy, the control of trace elements is crucial to the quality of the alloy. At present, there is no unified national standard or industry standard for the determination of titanium in silicon-aluminum alloy. The literature and patent methods are currently mainly based on acid dissolution. The reagents mainly include nitric acid, hydrofluoric acid, perchloric acid, sulfuric acid and other acids. During the dissolution process, highly corrosive and highly volatile acids pose serious environmental pollution. There are also some alkaline dissolution processes, but there are problems such as incomplete dissolution, cumbersome methods, long cycles, and not suitable for rapid analysis of large quantities of samples. Therefore, there is room for improvement in the detection of titanium content in silicon-aluminum alloys. Summary of the invention
[0004] The purpose of the present invention is to provide a method for detecting titanium content in silicon aluminum alloy to solve the problems raised in the above background technology that the existing method of dissolving by acid causes environmental pollution and the alkaline method is not conducive to rapid analysis of samples.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for detecting titanium content in silicon aluminum alloy, comprising the following steps:
[0006] S01: Sample dissolution, mix anhydrous sodium carbonate particles and boric acid powder in a mass ratio of 2:1 and grind them thoroughly until there are no obvious particles, weigh 0.1g of silicon-aluminum alloy sample respectively, add 0.45g of mixed alkali reagent, mix well and place in filter paper, wrap into small balls, put into a 30ml porcelain crucible with graphite in advance, slowly heat to 800℃, take out after melting for 20 minutes, sweep away the graphite after cooling, put 100ml (15:85) nitric acid in a 250ml beaker, heat it on an electric furnace, put the sample with the graphite swept away in the beaker for hot immersion, add 3-5 drops of hydrogen peroxide, heat to a uniform large bubble state (20min) after the solid is completely dissolved, cool to room temperature, filter into a 100ml volumetric flask, make up to volume, and shake well to obtain a silicon-aluminum alloy sample solution.
[0007] S02: Standard curve drawing. According to the content of titanium in the sample to be tested, a standard curve with a titanium content of 0 mg / L, 0.5 mg / L, 1 mg / L, 1.5 mg / L, 2 mg / L, 2.5 mg / L, and 3 mg / L was drawn. Use 1000 mg / L titanium dioxide standard solution, first prepare an intermediate solution with a titanium content of 10 mg / L, and respectively transfer 0 ml, 2.5 ml, 5 ml, 7.5 ml, 10 ml, 12.5 ml, and 15 ml of the intermediate solution to a 50 ml volumetric flask, dilute to 25 ml with water, add 4.6 ml of hydrochloric acid solution, 5 ml of 0.2% ascorbic acid solution, and 10 ml of 2.5% diantipyrine methane solution, and dilute to the scale line. After color development for 30 minutes, use the blank solution as a reference, use a UV-visible spectrophotometer to measure its absorbance at a wavelength of 380 nanometers, and draw a standard curve with Ti concentration as the horizontal coordinate and absorbance as the vertical coordinate.
[0008] S03: Determination of titanium in silicon-aluminum alloy sample, take 2ml of silicon-aluminum alloy sample solution into a 50ml volumetric flask, dilute it to 25ml with water, add 4.6ml hydrochloric acid solution, 5ml0.2% ascorbic acid solution, add 10ml2.5% diantipyrine methane solution, dilute to the scale line, after color development for 30 minutes, use blank solution as reference, and use UV-visible spectrophotometer to measure its absorbance at a wavelength of 380 nanometers.
[0009] Preferably, in S01, 0.1 g of the silicon-aluminum alloy sample is weighed to 0.0001 g, and the nitric acid solution is prepared by taking 15 ml of the nitric acid solution into a volumetric flask, and then adding H2O to make the volume to 100 ml and shaking it for use.
[0010] Preferably, the ascorbic acid solution in S02 and S03 is prepared by weighing 0.2000 g of ascorbic acid, dissolving it in 100 ml of water, shaking it well, and preparing it on the same day. The hydrochloric acid in S02 and S03 is commercially available hydrochloric acid with a concentration of 36%. The diantipyrine methane solution in S02 and S03 is prepared by weighing 6.25 g of diantipyrine methane, dissolving it in 2 mol / L hydrochloric acid and making up to 250 ml, shaking it well for later use.
[0011] Preferably, the anhydrous sodium carbonate particles and boric acid powder in S01 are fully ground and mixed in a grinder, and 0.1008 g of sample A and 0.1006 g of sample B are weighed for the silicon-aluminum alloy samples, respectively.
[0012] Preferably, the grinder comprises a grinding and mixing box, a connecting cover is provided on the top of the grinding and mixing box, a material receiving box is slidably connected to the inside of the grinding and mixing box, and a filter paper body is provided inside the material receiving box, an external threaded seat is fixed to the upper surface of the grinding and mixing box, and a support ring is provided on the inner side of the external threaded seat, a filter screen frame is provided on the upper surface of the support ring, and a rotating seat is rotatably connected to the inside of the filter screen frame, a stirring seat is slidably connected to the inside of the grinding and mixing box, and the stirring seat is located above the material receiving box, a stirring chamber is provided inside the stirring seat, and an electromagnetic valve is provided at the lower end of the inner side of the stirring chamber, a rotating rod is provided at the bottom end of the filter screen frame, and the rotating rod is located at the stirring Above the seat, stirring rods are arranged on both sides of the rotating rod, and a scraper B is arranged on the lower surface of the stirring rod, and a stirring blade is fixed on the lower surface of the scraper B, a supporting assembly is arranged inside the grinding and mixing box, a motor and a feeding seat are arranged on both sides of the upper surface of the connecting cover, a crushing blade is arranged inside the connecting cover, and a scraper A is arranged on the lower surface of the crushing blade, and blocks are fixed on the lower surface of the scraper A and the upper surface of the rotating rod, slots B are arranged at both ends of the rotating seat, and the slots B are engaged with the blocks, an internal thread groove is arranged on the inner side of the connecting cover, and the internal thread groove is threadedly connected to the external thread seat, and a reinforcement mechanism is arranged inside the connecting cover.
[0013] Preferably, the reinforcement mechanism includes an installation groove arranged inside the connecting cover, and a spring A is connected to one side of the installation groove, a moving block A is fixed to the other end of the spring A, and the moving block A is slidably connected to the installation groove, a limiting block is arranged on the lower surface of the moving block A, a pressing rod is fixed on the side of the moving block A away from the spring A, and the pressing rod extends to the outside of the connecting cover, a limiting seat is fixed to the outside of the external threaded seat, and an annular limiting groove is arranged inside the limiting seat, and the limiting block is rotatably connected to the annular limiting groove.
[0014] Preferably, the bottom of the limit block close to one side of the push rod is arranged in an inclined shape, and the reinforcement mechanism is provided in two groups, and the reinforcement mechanism is symmetrically arranged with respect to the filter frame.
[0015] Preferably, four groups of limit seats are fixed on the upper surface of the support ring, and four groups of slots A are provided on the lower surface of the filter frame, and the slots A are all engaged with the limit seats, and the size of the slots A is adapted to the size of the limit seats.
[0016] Preferably, the supporting assembly includes a receiving groove arranged on the inner wall of the grinding and mixing box, a spring B is fixed to the top of the receiving groove, and a moving block B is fixed to the other end of the spring B, a connecting rod is fixed to one side of the moving block B, a fixed seat is fixed to the side of the connecting rod away from the moving block B, the rotating rod passes through the interior of the fixed seat, a rotating groove is arranged on the inner wall of the fixed seat, a rotating ring is fixed to the outer surface of the rotating rod, and the rotating ring is rotatably connected to the rotating groove.
[0017] Preferably, the connecting rod, the moving block B and the spring B are arranged in a cross shape with respect to the fixing seat, and the cross-section of the connecting rod is circular.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The invention provides a method for detecting titanium content in silicon aluminum alloy. In the prior art, the method of dissolving by acid has the disadvantages of environmental pollution and the disadvantages of dissolving by alkali method is not conducive to rapid analysis of samples. Anhydrous sodium carbonate and boric acid are mixed and ground, and the mixture is rapidly melted with the sample at high temperature. The melt is leached with nitric acid, diantipyrine methane is used as a color developer, and the absorbance of the solution is determined by spectrophotometry to calculate the titanium content. The method is not only simple to operate, uses less drugs and equipment, but also has high detection efficiency and high accuracy, and is suitable for rapid batch detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 Schematic diagram of the method for detecting titanium content in silicon aluminum alloy of the present invention;
[0022] Figure 2 It is a schematic diagram of the titanium standard curve of the present invention;
[0023] Figure 3 It is the analysis result and precision schematic diagram of the present invention;
[0024] Figure 4 It is a schematic diagram of the three-dimensional structure of the grinding machine of the present invention;
[0025] Figure 5 It is a schematic diagram of the front cross-section structure of the present invention;
[0026] Figure 6 It is a schematic diagram of the front cross-section structure of the filter frame of the present invention;
[0027] Figure 7 It is a schematic diagram of the three-dimensional structure of the support assembly of the present invention;
[0028] Figure 8 It is a schematic diagram of the three-dimensional structure of the rotating rod distribution of the present invention;
[0029] Fig. 9 It is a schematic diagram of the three-dimensional structure of the reinforcement mechanism of the present invention.
[0030] Explanation of the reference numerals in the figure: 1. Grinding and mixing box; 11. External thread seat; 12. Support ring; 13. Limit seat; 14. Annular limit groove; 2. Connecting cover; 21. Feed seat; 22. Motor; 23. Internal thread groove; 24. Scraper A; 25. Crushing blade; 3. Material collecting box; 31. Filter paper body; 4. Reinforcement mechanism; 41. Spring A; 42. Moving block A; 43. Press rod; 44. Limit block; 5. Stirring seat; 51. Solenoid valve; 52. Stirring chamber; 6. Rotating rod; 61. Rotating ring; 62. Stirring rod; 63. Scraper B; 64. Stirring blade; 7. Support assembly; 71. Fixed seat; 72. Spring B; 73. Moving block B; 74. Connecting rod; 75. Rotating groove; 8. Filter frame; 81. Slot A; 82. Rotating seat; 83. Slot B; 9. Block. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of the embodiments. Based on the embodiments of the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.
[0032] Embodiment 1
[0033] In order to solve the problems in the prior art that the acid dissolution method causes environmental pollution and the alkali method is not conducive to rapid analysis of samples, the following scheme is disclosed. Figure 1 and Figure 2 As shown:
[0034] A method for detecting titanium content in silicon aluminum alloy comprises the following steps:
[0035] S01: Sample dissolution, mix anhydrous sodium carbonate particles and boric acid powder in a mass ratio of 2:1 and grind them thoroughly until there are no obvious particles, weigh 0.1g of silicon-aluminum alloy sample respectively, add 0.45g of mixed alkali reagent, mix well and place in filter paper, wrap into small balls, put into a 30ml porcelain crucible with graphite in advance, slowly heat to 800℃, take out after melting for 20 minutes, sweep away the graphite after cooling, put 100ml (15:85) nitric acid in a 250ml beaker, heat it on an electric furnace, put the sample with the graphite swept away in the beaker for hot immersion, add 3-5 drops of hydrogen peroxide, heat to a uniform large bubble state (20min) after the solid is completely dissolved, cool to room temperature, filter into a 100ml volumetric flask, make up to volume, and shake well to obtain a silicon-aluminum alloy sample solution.
[0036] S02: Standard curve drawing. According to the content of titanium in the sample to be tested, a standard curve with a titanium content of 0 mg / L, 0.5 mg / L, 1 mg / L, 1.5 mg / L, 2 mg / L, 2.5 mg / L, and 3 mg / L was drawn. Use 1000 mg / L titanium dioxide standard solution, first prepare an intermediate solution with a titanium content of 10 mg / L, and respectively transfer 0 ml, 2.5 ml, 5 ml, 7.5 ml, 10 ml, 12.5 ml, and 15 ml of the intermediate solution to a 50 ml volumetric flask, dilute to 25 ml with water, add 4.6 ml of hydrochloric acid solution, 5 ml of 0.2% ascorbic acid solution, and 10 ml of 2.5% diantipyrine methane solution, and dilute to the scale line. After color development for 30 minutes, use the blank solution as a reference, use a UV-visible spectrophotometer to measure its absorbance at a wavelength of 380 nanometers, and draw a standard curve with Ti concentration as the horizontal coordinate and absorbance as the vertical coordinate.
[0037] S03: Determination of titanium in silicon-aluminum alloy sample, take 2ml of silicon-aluminum alloy sample solution into a 50ml volumetric flask, dilute it to 25ml with water, add 4.6ml hydrochloric acid solution, 5ml0.2% ascorbic acid solution, add 10ml2.5% diantipyrine methane solution, dilute to the scale line, after color development for 30 minutes, use blank solution as reference, and use UV-visible spectrophotometer to measure its absorbance at a wavelength of 380 nanometers.
[0038] In S01, 0.1g of the silicon-aluminum alloy sample is weighed to 0.0001g, the nitric acid solution is prepared by taking 15ml of nitric acid solution and adding it to a volumetric flask, and diluting it to 100ml with H2O, shaking it well for later use, the ascorbic acid solution in S02 and S03 is prepared by weighing 0.2000g of ascorbic acid, dissolving it in 100ml of water, shaking it well, and preparing it on the same day, the hydrochloric acid in S02 and S03 is commercially available hydrochloric acid with a concentration of 36%, the diantipyrine methane solution in S02 and S03 is prepared by weighing 6.25g of diantipyrine methane, dissolving it in 2mol / L hydrochloric acid, diluting it to 250ml, shaking it well for later use, the anhydrous sodium carbonate particles and boric acid powder in S01 are fully ground and mixed in a grinder, and the silicon-aluminum alloy samples are weighed as 0.1008g of sample A and 0.1006g of sample B, respectively.
[0039] The concentration of Ti is found from the standard curve, and the content of titanium in the sample is calculated according to the following formula: middle, : Titanium concentration obtained from the working curve, : titanium concentration of blank sample; : The volume of color development and volume setting, : The volume of the sample to be dissolved and fixed, ; The volume of the aluminum alloy sample solution transferred for color development, m: the mass of the solid sample weighed.
[0040] Actual sample calculation:
[0041] Sample Sample A: =4.11%
[0042] Sample Sample B: =1.33%
[0043] In the above, standard samples with different contents were selected and each sample was analyzed 6 times in parallel. The analysis results and precision are shown in Figure 3 As shown;
[0044] By comparing the actual sample results with those of the external testing agency's laboratory, the error was less than 5%; the RSD was less than 2%, both of which were in line with the relevant provisions of GB / T27417-2017 "Guidelines for Confirmation and Validation of Chemical Analysis Methods for Conformity Assessment". Therefore, anhydrous sodium carbonate and boric acid were mixed and ground, quickly melted with the sample at high temperature, and the melt was extracted with nitric acid. Diantipyrine methane was used as a color developer, and the absorbance of the solution was determined by spectrophotometry to calculate the titanium content. This method is not only easy to operate, uses less drugs and equipment, but also has high detection efficiency and high accuracy, and is suitable for rapid batch detection.
[0045] Embodiment 2
[0046] In order to evenly mix the raw materials while crushing them, the following scheme is disclosed, specifically: Figures 4 to 9 As shown:
[0047] The grinding machine includes a grinding and mixing box 1, a connecting cover 2 is arranged above the grinding and mixing box 1, a material receiving box 3 is slidably connected inside the grinding and mixing box 1, and a filter paper body 31 is arranged inside the material receiving box 3, an external threaded seat 11 is fixed on the upper surface of the grinding and mixing box 1, and a support ring 12 is arranged on the inner side of the external threaded seat 11, a filter screen frame 8 is arranged on the upper surface of the support ring 12, and a rotating seat 82 is rotatably connected inside the filter screen frame 8, a stirring seat 5 is slidably connected inside the grinding and mixing box 1, and the stirring seat 5 is located above the material receiving box 3, a stirring chamber 52 is arranged inside the stirring seat 5, and a solenoid valve 51 is arranged at the lower end of the inner side of the stirring chamber 52, a rotating rod 6 is arranged at the bottom end of the filter screen frame 8, and the rotating rod 6 is located above the stirring seat 5, and the rotating rod 6 is arranged above the stirring seat 5. Stirring rods 62 are provided on both sides of the rod 6, and a scraper B63 is provided on the lower surface of the stirring rod 62, and a stirring blade 64 is fixed on the lower surface of the scraper B63. A support assembly 7 is provided inside the grinding and stirring box 1, and a motor 22 and a feed seat 21 are provided on both sides of the upper surface of the connecting cover 2, respectively. A crushing blade 25 is provided inside the connecting cover 2, and a scraper A24 is provided on the lower surface of the crushing blade 25, and a clamping block 9 is fixed on the lower surface of the scraper A24 and the upper surface of the rotating rod 6. A clamping groove B83 is provided at both ends of the rotating seat 82, and the clamping groove B83 is engaged with the clamping block 9. An internal thread groove 23 is provided on the inner side of the connecting cover 2, and the internal thread groove 23 is threadedly connected to the external thread seat 11, and a reinforcement mechanism 4 is provided inside the connecting cover 2. The reinforcement mechanism 4 includes a mounting groove arranged inside the connection cover 2, and a spring A41 is connected to one side of the mounting groove, a moving block A42 is fixed to the other end of the spring A41, and the moving block A42 is slidably connected to the mounting groove, a limiting block 44 is arranged on the lower surface of the moving block A42, a pressing rod 43 is fixed to the side of the moving block A42 away from the spring A41, and the pressing rod 43 extends to the outside of the connection cover 2, a limiting seat 13 is fixed to the outside of the external thread seat 11, and an annular limiting groove 14 is arranged inside the limiting seat 13, the limiting block 44 is rotatably connected to the annular limiting groove 14, and the bottom of the limiting block 44 close to the pressing rod 43 is arranged in an inclined shape, and the reinforcement mechanism 4 is provided with two groups, and the reinforcement mechanism 4 is symmetrically arranged about the filter frame 8. Four groups of limit seats 13 are fixed on the upper surface of the support ring 12, and four groups of card slots A81 are arranged on the lower surface of the filter frame 8, and the card slots A81 are all engaged with the limit seats 13, and the size of the card slots A81 is adapted to the size of the limit seats 13. The support assembly 7 includes a receiving groove arranged on the inner wall of the grinding and mixing box 1, a spring B72 is fixed to the groove top of the receiving groove, and a moving block B73 is fixed to the other end of the spring B72, a connecting rod 74 is fixed to one side of the moving block B73, and a fixed seat 71 is fixed to the side of the connecting rod 74 away from the moving block B73, the rotating rod 6 passes through the interior of the fixed seat 71, and a rotating groove 75 is arranged on the inner wall of the fixed seat 71, and a rotating ring 61 is fixed to the outer surface of the rotating rod 6, and the rotating ring 61 is rotatably connected with the rotating groove 75,The connecting rod 74, the moving block B73 and the spring B72 are arranged in a cross shape with respect to the fixing seat 71. The cross section of the connecting rod 74 is circular.
[0048] In this embodiment, when it is necessary to mix and crush the anhydrous sodium carbonate particles and the boric acid powder, a certain amount of anhydrous sodium carbonate particles and boric acid powder are put into the grinding and mixing box 1 through the feeding seat 21, and the motor 22 is started to crush the anhydrous sodium carbonate particles and the boric acid powder under the action of the crushing blade 25 and the scraper A24 until there are no obvious particles falling into the mixing seat 5. During the rotation of the crushing blade 25 and the scraper A24, the rotating rod 6 is driven to rotate under the cooperation of the block 9 and the rotating seat 82, so as to achieve the stirring and mixing of the crushed anhydrous sodium carbonate particles and the boric acid powder, improve the uniformity of the mixing, and finally turn on the electromagnetic. Valve 51 allows the mixture to fall onto the top of the filter paper body 31 for material collection. By facilitating subsequent experimental operations, when parts need to be replaced, the push rod 43 is pressed by hand to move the limit block 44 out of the annular limit groove 14, and the connecting cover 2 is rotated to separate the connecting cover 2 as a whole from the grinding and mixing box 1. Under the elastic reset action of the spring B72, the filter frame 8 is pushed out of the grinding and mixing box 1, and the stirring blade 64 and the scraper B63 are moved out of the stirring seat 5, which facilitates the separation of the stirring seat 5 and the filter frame 8 from the grinding and mixing box 1. The reverse operation is performed to achieve combination, and local small parts are replaced, which is beneficial to reducing the overall maintenance cost.
[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for detecting titanium content in silicon aluminum alloy, characterized in that: The steps include: S01: Sample dissolution, mix anhydrous sodium carbonate particles and boric acid powder in a mass ratio of 2:1 and grind thoroughly until there are no obvious particles, weigh 0.1g of silicon aluminum alloy sample respectively, add 0.45g of mixed alkali reagent, mix well and place in filter paper, wrap into small balls, put into a 30ml porcelain crucible with graphite in advance, slowly heat to 800℃, take out after melting for 20 minutes, sweep away the graphite after cooling, put 100ml of 15:85 nitric acid in a 250ml beaker, heat it on an electric furnace, put the sample with the graphite swept away in the beaker for hot leaching, add 3-5 drops of hydrogen peroxide, heat to a uniform large bubble state for 20min after the solid is completely dissolved, cool to room temperature, filter in a 100ml volumetric flask, make up to volume, and shake well to obtain a silicon aluminum alloy sample solution; The anhydrous sodium carbonate particles and boric acid powder were fully ground and mixed in a grinder, and 0.1008 g of sample A and 0.1006 g of sample B were weighed for the silicon-aluminum alloy samples respectively; S02: standard curve drawing, according to the content of titanium in the sample to be tested, draw a standard curve with a titanium content of 0mg / L, 0.5mg / L, 1mg / L, 1.5mg / L, 2mg / L, 2.5mg / L, and 3mg / L; use 1000mg / L titanium dioxide standard solution, first prepare an intermediate solution with a titanium content of 10mg / L, respectively take 0ml, 2.5ml, 5ml, 7.5ml, 10ml, 12.5ml, and 15ml of the intermediate solution and put it into a 50ml volumetric flask, dilute it to 25ml with water, add 4.6ml hydrochloric acid solution, 5ml0.2% ascorbic acid solution, add 10ml2.5% diantipyrine methane solution, and make up to the scale line. After color development for 30 minutes, use a blank solution as a reference, use a UV-visible spectrophotometer to measure its absorbance at a wavelength of 380 nanometers, and draw a standard curve with Ti concentration as the horizontal coordinate and absorbance as the vertical coordinate; S03: Determination of titanium in silicon-aluminum alloy sample, take 2ml of silicon-aluminum alloy sample solution into a 50ml volumetric flask, dilute to 25ml with water, add 4.6ml hydrochloric acid solution, 5ml 0.2% ascorbic acid solution, add 10ml 2.5% diantipyrine methane solution, dilute to the scale line, after color development for 30 minutes, use blank solution as reference, use UV-visible spectrophotometer, measure its absorbance at a wavelength of 380 nanometers; The grinding machine comprises a grinding and stirring box (1), a connecting cover (2) is arranged above the grinding and stirring box (1), a material receiving box (3) is slidably connected inside the grinding and stirring box (1), and a filter paper body (31) is arranged inside the material receiving box (3), an external thread seat (11) is fixed on the upper surface of the grinding and stirring box (1), and a support ring (12) is arranged on the inner side of the external thread seat (11), a filter screen frame (8) is arranged on the upper surface of the support ring (12), and a rotating seat (82) is rotatably connected inside the filter screen frame (8), a stirring seat (5) is slidably connected inside the grinding and stirring box (1), and the stirring seat (5) is located above the material receiving box (3), a stirring chamber (52) is arranged inside the stirring seat (5), and a lower portion of the inner side of the stirring chamber (52) is provided. A solenoid valve (51) is provided at the end, a rotating rod (6) is provided at the bottom end of the filter frame (8), and the rotating rod (6) is located above the stirring seat (5), stirring rods (62) are provided on both sides of the rotating rod (6), and a scraper B (63) is provided on the lower surface of the stirring rod (62), and a stirring blade (64) is fixed on the lower surface of the scraper B (63), a supporting assembly (7) is provided inside the grinding and stirring box (1), a motor (22) and a feeding seat (21) are provided on both sides of the upper surface of the connecting cover (2), a crushing blade (25) is provided inside the connecting cover (2), and a scraper A (24) is provided on the lower surface of the crushing blade (25), and a clamping block (9) is fixed on the lower surface of the scraper A (24) and the upper surface of the rotating rod (6), and the rotating Both ends of the seat (82) are provided with a card slot B (83), and the card slot B (83) is engaged with the card block (9), the inner side of the connection cover (2) is provided with an internal thread groove (23), and the internal thread groove (23) is threadedly connected to the external thread seat (11), and the connection cover (2) is provided with a reinforcement mechanism (4), the reinforcement mechanism (4) includes a mounting groove provided inside the connection cover (2), and a spring A (41) is connected to one side of the mounting groove, a moving block A (42) is fixed to the other end of the spring A (41), and the moving block A (42) is slidably connected to the mounting groove, a limit block (44) is provided on the lower surface of the moving block A (42), and a push rod (43) is fixed to the side of the moving block A (42) away from the spring A (41), and The push rod (43) extends to the outside of the connecting cover (2); a limiting seat (13) is fixed to the outside of the external thread seat (11); an annular limiting groove (14) is provided inside the limiting seat (13); the limiting block (44) is rotatably connected to the annular limiting groove (14); the supporting assembly (7) comprises a receiving groove provided on the inner wall of the grinding and mixing box (1); a spring B (72) is fixed to the top of the receiving groove; a moving block B (73) is fixed to the other end of the spring B (72); a connecting rod (74) is fixed to one side of the moving block B (73); a fixed seat (71) is fixed to the side of the connecting rod (74) away from the moving block B (73); the rotating rod (6) passes through the inside of the fixed seat (71); a rotating groove (75) is provided on the inner wall of the fixed seat (71);A rotating ring (61) is fixed to the outer surface of the rotating rod (6), and the rotating ring (61) is rotatably connected to the rotating groove (75).
2. The method for detecting titanium content in a silicon aluminum alloy according to claim 1, characterized in that: In S01, 0.1g of silicon-aluminum alloy sample is weighed to 0.0001g. The nitric acid solution is prepared by taking 15ml of nitric acid solution into a volumetric flask, and then diluting it to 100ml with H2O and shaking it for use.
3. The method for detecting titanium content in a silicon aluminum alloy according to claim 1, characterized in that: The preparation method of ascorbic acid solution in S02 and S03 is as follows: weigh 0.2000g ascorbic acid, dissolve it in 100ml water, shake well, and prepare it on the same day. The hydrochloric acid in S02 and S03 is commercially available hydrochloric acid with a concentration of 36%. The preparation method of diantipyrine methane solution in S02 and S03 is as follows: weigh 6.25g diantipyrine methane, dissolve it in 2mol / L hydrochloric acid and make up to 250ml, shake well and set aside.
4. The method for detecting titanium content in a silicon aluminum alloy according to claim 1, characterized in that: The bottom of the limit block (44) close to the push rod (43) is arranged in an inclined shape. Two groups of reinforcement mechanisms (4) are arranged. The reinforcement mechanisms (4) are symmetrically arranged with respect to the filter screen frame (8).
5. The method for detecting titanium content in a silicon aluminum alloy according to claim 1, characterized in that: Four groups of limit seats (13) are fixed on the upper surface of the support ring (12), and four groups of slots A (81) are provided on the lower surface of the filter screen frame (8). The slots A (81) are all engaged and connected with the limit seats (13), and the size of the slots A (81) is adapted to the size of the limit seats (13).
6. The method for detecting titanium content in silicon aluminum alloy according to claim 1, characterized in that: The connecting rod (74), the moving block B (73) and the spring B (72) are arranged in a cross shape with respect to the fixing seat (71), and the cross section of the connecting rod (74) is arranged in a circular shape.
Citation Information
Patent Citations
Method for rapidly determining titanium content in metallurgical iron material
CN105092565A